KETERKAITAN PERCEPTION OF INTERNAL ENVIRONMENTAL UNCERTAINTY TERHADAP INTENTION TO CONTINUE - Sri Vandayuli Riorini; Robert Kristaung (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2008)
This research is observing about the Perception of internal environthental uncertainty to Service Performance, and then Service performance to Satisfaction, and then Satisfaction to Intention to Continue. Data was gathered by spreading the questionnaire to 130 respondents who manager from service industry to using provider mobile phone. The sampling technique was using a purposive sampling. The analysis tool used was Structural Equation Modeling using Amos version 16 software. The hypothesis testing result shows that Perception of internal environmental uncertainty has a negative effect to Service Performance, and Service performance has a positive effect to Satisfaction, later Satisfaction has a positive effect to Intentions to Continue. It is hoped for the next research to explore another services industry beside and also adds another variable which also has an effect to the variables observed by this research.Keywords : Perception of internal Environmental Uncertainty, Serv ce Performance, Satisfaction, Intention to Continue